Coup de Grace: How the Quad is Hastening the Destruction of ASEAN - Quinissa Putrirezhy (Journal Of Global Strategic Studies, 2021)
The rise of the US-led Quad alliance in 2017 will be a test for ASEAN. Southeast Asia is at the center of a simmering strategic rivalry between the two world superpowers, the US and China. China's meteoric economic ascendence on the global stage has shifted the balance of global power in today's geopolitics. This article seeks to examine the potential of how the Quad may shake the ASEAN's unity and centrality as a result of China's rise. Beijing has expanded its influence throughout Southeast Asia and is by now easily ASEAN's largest trading partner, while at the same time it has aggressively asserted its pseudohistorical irredentist claims in the South China Sea, a vital route for regional trade, creating territorial disputes with some ASEAN member countries. This article found that the geopolitical situation in Southeast Asia is likely to grow more difficult, perhaps affecting Southeast Asia's policy of non-alignment. Some argue that the Quad will bring balance in the Asia Pacific; however, this view will inevitably change if some ASEAN countries in favor of FOIP decide to join the Quad, either formally or informally, and work together to attempt to counterbalance China, which would leave ASEAN itself torn apart.